1976
DOI: 10.1159/000136578
|View full text |Cite
|
Sign up to set email alerts
|

Serum Sialic Acid Levels in Lung Cancer Patients

Abstract: The levels of N-acetyl neuraminic acid (sialic acid) in normal men and pre-and post-menopausal women were determined. Smoking, post-menopausal estrogen therapy, oral contraceptives, and refreezing had no effects on sialic acid levels. Pre-treatment values from patients with lung carcinoma showed markedly elevated levels of sialic acid (0.697 ± 0.149 μM/ml) as compared to those from normal controls (0.432 ± 0.067 μM/ml). The potential usefulness of sialic acid as a biological marker is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

1983
1983
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 4 publications
1
16
0
1
Order By: Relevance
“…In cancer, these sialylated conjugates protect malignant cells from cellular defense systems. Elevated levels of NANA have been found in various cancer types, including lung cancer (49). Sialic acid as a blood biomarker for prognosis has been assessed with mixed results, although, to our knowledge, not in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, these sialylated conjugates protect malignant cells from cellular defense systems. Elevated levels of NANA have been found in various cancer types, including lung cancer (49). Sialic acid as a blood biomarker for prognosis has been assessed with mixed results, although, to our knowledge, not in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 5639 (21%) men and 3307 (12%) women died during the follow up period, in whom death in 3052 (54%) men and 1368 (41%) women was from cardiovascular causes. During short (0-6 years), medium (7-13 years), and long (14)(15)(16)(17)(18)(19)(20) years) term follow up the relative risk of death from cardiovascular disease increased with increasing serum sialic acid concentration. The relative risk (95% confidence interval) associated with the highest quartile of sialic acid concentration compared with the lowest quartile was 2-38 (2-01 to 2.83) in men and (1-93 to 3.57) in women.…”
Section: Introductionmentioning
confidence: 99%
“…Krolikowski et al (1976) showed that there is a significant difference in the levels of sialic acid in patients with lung cancer compared to normal controls. Hence they reported sialic acid to be of value as a biologic marker in lung cancer [12]. Seber et al (1989) also showed that sialic acid levels in BAL fluid were highly correlated with the diagnosis of bronchial cancer [13].…”
Section: Discussionmentioning
confidence: 99%